ESTOWER: an expert system for the thermal design of wet cooling towers - Mohiuddin, A. K. M.; Kant, Keshav; Sangal, Rajeev (Elsevier Science Ltd., 1996)
An expert system based on logic programming has been developed, using a systematic procedure for the thermal design of natural and mechanical draft wet cooling towers of the counterflow and crossflow types. The present system is based on a rule-based system. The "VIDHI", expert-system shell written in LISP, has been used as a tool to develop the present system. The "VIDHI" shell is based on backward chaining. The inference mechanism of the system is similar to that of PROLOG. The rule set of the expert system was developed by using a tree structure for the entire design process. Besides designing a cooling tower for a given situation, the expert system can also be used for teaching and learning about cooling-tower design.